PERBEDAAN KADAR KOLESTEROL TOTAL PADA PASIEN PUASA DAN TIDAK PUASA - Sinta Nur Ifaliza; Ardiya Garini; Asrori Asrori (Klinikal Sains : Jurnal Analis Kesehatan, 2021)
Cholesterol is a fatty substance produced by the liver. Cholesterol can be found throughout the body and plays an important role in daily body functions. Cholesterol tests carried out in the laboratory are one of the parameters to determine heart disease. Cholesterol serum levels is used as an indicator of coronary artery disease and atherosclerosis. Since the fatigue can affect the examination result, patients should not perfom heavy activities during 24 hours before the examination. Objective :to know the difference of total cholesterol level on fasting and non fasting patients. Method :it was an analytical research with one group pre and posttest design. This research was conducted in March 2020. The population were all the 1st and 2nd grade students of the Medical Laboratory Technology Department of Health Polytechnic of Palembang. Samples were taken by simple random sampling. Paired t-test was used as a statistic analysis. Pursuant to result t test of data obtained by p value = 0,134 (p > 0,05) means there is no significant difference of fasting cholesterol levels and non-fasting cholesterol levels.